2000
DOI: 10.1177/004051750007001109
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Measurements of the Main Mechanical Parameters of Knitted Fabrics

Abstract: Mechanical parameters such as bending rigidity, thickness, compressibility, and coefficient of friction are measured by a sensory method for a series of plain and rib weft knitted structures made from cashmere and polyester textured yarns. The values estimated by the sensory method are found to be in fairly good agreement with the values measured on the KES system. The results of our work indicate that by using a standard and controlling the handling manner, sensory assessments can be as successfully quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…The mechanical and surface properties of fabrics have been studied in the context of end-users choice and satisfaction, leading to a series of investigations looking at the relation between objective and subjective assessments (Alimaa et al 2000;Cardello et al 2003;Sular and Okur 2007). On the other hand, in the current study fabric texture properties will be evaluated to assess whether these influence the tactile cues underlying skin wetness perception.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and surface properties of fabrics have been studied in the context of end-users choice and satisfaction, leading to a series of investigations looking at the relation between objective and subjective assessments (Alimaa et al 2000;Cardello et al 2003;Sular and Okur 2007). On the other hand, in the current study fabric texture properties will be evaluated to assess whether these influence the tactile cues underlying skin wetness perception.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the compression energy, WC, was taken to characterize the compressibility of knitted fabrics. In our study [7] " Sensory Measurement of Main Mechanical Properties of Knitted Fabrics", we found that sensory softness/hardness was consistently correlated with only WC among the other existing, instrumental parameters such as WC/ TMAx and relative strain, EMC.…”
Section: Compression Curvementioning
confidence: 70%
“…The average estimate of the evaluator preference was calculated according to a standard paired-comparison test. 16 There was a significant difference of smoothness between the samples ( Figure 12). According to the evaluators' assessment for smoothness, the fabric R4 from ring-spun yarn Ry4 had the smoothest surface, and fabric R5 made from open-end yarn (Ry5) had the roughest surface among the samples.…”
Section: Resultsmentioning
confidence: 95%